Knowledge management and higher education : a critical analysis - Metcalfe, Amy, 1967- (Hershey: Information Science Pub., 2006)
'Using various social science perspectives, this book provide critical analyses of knowledge management in higher education, with an emphasis on unintended consequences and future implications'--Provided by publisher.
Includes bibliographical references (p. 316-340) and index.
Keywords: Education, Higher -- Economic aspects; Knowledge management; Education, Higher -- Effect of technological innovations on